Gene networks in basal cell carcinoma of the eyelid, analyzed using gene expression profiling - Yunoki, Tatsuya (Oncol Lett, 2018)
Basal cell carcinoma (BCC) is the most frequent malignant tumor of the eyelid; it progresses slowly and rarely metastasizes. However, BCC of the eyelid is partially invasive and can extend to the surrounding ocular adnexa even if appropriate treatment is performed. To understand the molecular mechanism underlying its pathogenesis, global gene expression analysis of surgical tissue samples of BCC of the eyelid (n=2) and normal human epidermal keratinocytes was performed using a GeneChip(®) system. The histopathological examination of surgically removed eyelid tissues showed the tumor nest composed with small basaloid. In the samples from patients 1 and 2, 687 and 713 genes were identified, respectively, demonstrating ≥5.0-fold higher expression than that noted in normal human epidermal keratinocytes. For the 640 genes with upregulated expression in both patient samples, Ingenuity(®) pathway analysis showed that the gene network in BCC of the eyelid included many BCC-associated genes, such as the following: BCL2 apoptosis regulator; Patched-1; and SRY-box 9. In addition, unique gene networks related to cancer cell growth, tumorigenesis, and cell survival were identified. These results of integrating microarray analyses provide further insights into the molecular mechanisms involved in BCC of the eyelid and may provide a therapeutic approach for this disease.